1996
DOI: 10.1111/j.1365-2958.1996.tb02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Campylobacter fetus S‐layer protein diversity utilizes a single promoter on an invertible DNA segment

Abstract: Wild-type strains of Campylobacter fetus contain a monomolecular array of surface layer proteins (SLPs) and vary the antigenicity of the predominant SLP expressed. Reciprocal recombination events among the eight genomic SLP gene cassettes, which encode 97- to 149 kDa SLPs, permit this variation. To explore whether SLP expression utilizes a single promoter, we created mutant bacterial strains using insertional mutagenesis by rescue of a marker from plasmids. Experimental analysis of the mutants created clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 51 publications
4
67
0
Order By: Relevance
“…Cloning and sequencing of the S-protein genes of C. fetus 23D revealed that the different S-proteins originated from multiple S-protein genes. An active S-promoter was found upstream of the S-protein gene (sapA) for the wild-type strain (Dworkin and Blaser, 1996). Inversion of a 6.2 kb chromosomal segment containing the S-promoter leads to the expression of either one of the two S-protein genes (sapA or sapA2 ) surrounding this invertable segment (Fig.…”
Section: S-layer Variation and Silent S-protein Genesmentioning
confidence: 99%
“…Cloning and sequencing of the S-protein genes of C. fetus 23D revealed that the different S-proteins originated from multiple S-protein genes. An active S-promoter was found upstream of the S-protein gene (sapA) for the wild-type strain (Dworkin and Blaser, 1996). Inversion of a 6.2 kb chromosomal segment containing the S-promoter leads to the expression of either one of the two S-protein genes (sapA or sapA2 ) surrounding this invertable segment (Fig.…”
Section: S-layer Variation and Silent S-protein Genesmentioning
confidence: 99%
“…There is also increasing evidence that S-layer-carrying bacteria may use Slayer variation, by expressing alternative S-layer protein genes, for adaptation to different stress factors, such as the immune response of the host for pathogens and drastic changes in the environmental conditions for nonpathogens. In most of the characterized cases, the mechanism of S-layer variation is based on DNA rearrangements (4,8,26,29). Structural features of S layers also indicate that they may offer several advantages for different biotechnological applications.…”
mentioning
confidence: 99%
“…Third, mutagenesis studies (Blaser et al, 1994) indicated that SLP expression variation is associated with exchange of cassettes 3Ј to the sapA promoter. Fourth, spontaneous S ¹ mutant strains that have a 9 kb deletion including this promoter (Tummuru and Blaser, 1992;Fujita and Amako, 1994;Dworkin et al, 1995b), are unable to produce an S-layer under any circumstance tested, including strong in vivo and in vitro selection for the S þ phenotype (Dworkin and Blaser, 1996).…”
Section: Nature Of the Sapa Promotermentioning
confidence: 99%
“…Mapping of the phenotypic variants indicated chromosomal rearrangement due to inversion of a long (6.2 kb) segment of DNA containing this promoter (Dworkin and Blaser, 1996). Cloning and sequencing of the 6.2 kb promoter-containing invertible DNA element revealed a probable 5.6 kb operon of four overlapping ORFs of which three have predicted strong amino acid homologies to members of the RTX family of protein secretion (type I) pathway (Thompson et al, 1997).…”
Section: Nature Of the Sapa Promotermentioning
confidence: 99%
See 1 more Smart Citation